Climate Change and the Construction of Compromised Agency in Selected Contemporary Fiction - Murray, Jessica (Archīum Ateneo, 2024)
As the realities of climate change occupy an increasingly prominent position in all spheres of contemporary societies, the producers of cultural products grapple with these dynamics in their work. Even in texts where the climate and environmental concerns are tangential to the primary narratives, authors of contemporary fiction tend to make at least some passing reference to these dynamics. Fiction offers a space of almost limitless possibilities where writers can offer radically innovative modes of being in a world that is changing at an unprecedented rate due to anthropogenic activities. The construction of agency and the capacity of agents to engage meaningfully with a planet in crisis will serve as the focus points of this article. I will demonstrate how contemporary fiction successfully draws readers’ attention to the ubiquity of the climate crisis and the necessity of environmental engagement in various ways. However, I also suggest that these texts fail to meet the demands of this historical moment by mostly not moving beyond various articulations of the problem. In other words, they expose the environmental and epistemological challenges presented by the age of the Anthropocene, but they do not move much beyond this exposure to suggest meaningful modes of activisms. I will refer to novels that were published in 2022 and 2023 to illustrate how climate concerns are dismissed, relegated to the margins of conversations amongst primary protagonists, or associated with characters on the fringes of society. The selected novels are The Rabbit Hutch (2022) by Tess Gunty, Birnam Wood (2023) by Eleanor Catton, The Life of the Mind (2022) by Christine Smallwood and Eleutheria (2022) by Allegra Hyde.